Flow uneven-distribution and its impact on performances of forward osmosis module - Qing, L. (Elsevier Ltd, 2020)
Progresses on development of forward osmosis (FO) membrane should be accompanied with development of acceptable FO modules. Most flat-sheet FO membranes are assembled into the modified spiral wound module by introduction of an internal baffle which results in a U-shape flow path that allows flow uneven-distribution. This study assesses the flow uneven-distribution and its impact on a U-shape flow path and compares it with a straight flow path (I-shape), like the one in the plate-and-frame module. The flow distribution was visualized through the salt tracing test, dye tracing, computational fluid dynamics (CFD) simulation and particle image velocimetry (PIV). The performance of a bench-scale module of I-shape and U-shape was then assessed. Results from all visualization methods demonstrate large spatial flow variations in the U-shape flow path. However, it does not really affect the overall flux. The U-shape flow path benefits over the Ishape when operated at equal volumetric velocities. The I-shape path only shows higher fluxes by 21 and 3 when operated under equal cross flow velocities under active layer facing feed solution and active layer facing draw solution modes, respectively. The low fluxes in the U-shape flow path occur in the dead-zones. The flux variations in the U-shape flow path does not significantly affect the short-term membrane fouling but is expected to be more intense in the larger modules. A simple approach to combat flow uneven-distribution via inclusion of internal baffle can reduce uneven-distribution of flow. Â© 2019 Elsevier Ltd